Analisis Kepastian Hukum dalam Pembagian Warisan Terkait Ahli Waris yang Ditetapkan Afwezigheid oleh Pengadilan: Studi Putusan Pengadilan Indonesia - Muhammad Fa’iq Widyadana (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2026)
This study analyzes legal certainty in the distribution of inheritance involving heirs declared absent (Afwezigheid) by the court in Indonesia. The issue of inheritance distribution often becomes complex when one of the heirs is missing or whose whereabouts are unknown, resulting in legal uncertainty regarding the management and transfer of inherited assets. This research uses a normative juridical method through the analysis of several Indonesian court decisions related to Afwezigheid, including Decision Number 102/Pdt.P/2014/PN.Kpj, Decision Number 18/Pdt.P/2022/PN Pwr, Decision Number 46/Pdt.P/2022/PN Pwr, Decision Number 108/Pdt.P/2022/PN Unr, and Decision Number 173/Pdt.P/2025/PN Smr. The results show that the determination of Afwezigheid provides a legal basis for managing the property of absent persons through the supervision of the court and the Heritage Hall (Balai Harta Peninggalan). However, such determination does not eliminate the inheritance rights of the absent heir, but only postpones their implementation until legal certainty regarding the person’s status is obtained. Furthermore, if the absent person later reappears after the inheritance has been managed or transferred, they retain the right to reclaim their property or seek compensation in accordance with Article 479 of the Indonesian Civil Code. This condition demonstrates that legal certainty in inheritance distribution involving Afwezigheid remains conditional and requires more comprehensive regulations to balance the protection of heirs, third parties acting in good faith, and the rights of the absent person.